The Diphosphorus Complex [Cp2Mo2(CO)4(η2‐P2)] as a Building Block for the Synthesis of Mixed‐Hybrid Coordination Polymers. Issue 28 (29th August 2016) - Moussa, Mehdi Elsayed; Attenberger, Bianca; Fleischmann, Martin; Schreiner, Andrea; Scheer, Manfred
Abstract : The three‐component reaction of the tetrahedral diphosphorus complex [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (1 ), with Ag[BF4 ] (2 ) in the presence of 2, 2′‐bipyrimidine (3 ) leads to the formation of the two novel two‐dimensional networks4 and5 . Compound4 is a new two‐dimensional organometallic‐organic hybrid polymer, while derivative5 represents a unique two‐dimensional organometallic‐inorganic‐organic hybrid polymer. These results show the possibility of synthesizing a new class of coordination polymers, which could not be obtained from two‐component reactions with organic molecules in addition of metal ions. Abstract : A three‐component reaction of the diphosphorus complex [Cp2 Mo2 (CO)4 (η 2 ‐P2 )] (Cp = C5 H5 ), Ag[BF4 ], and 2, 2′‐bipyrimidine yielded two novel 2D hybrid polymers. One represents a 2D organometallic‐organic coordination polymer, while the other is a unique 2D organometallic‐inorganic‐organic coordination polymer.